The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1677-55382009000600007
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral resection of the prostate for the treatment of lower urinary tract symptoms related to benign prostatic hyperplasia: how much should be resected?

Abstract: Objective: To assess the impact of the percent of resected tissue on the improvement of urinary symptoms. Materials and Methods:The study included a prospective analysis of 88 men with benign prostatic hyperplasia. Patients were divided in three groups according to the percent of resected tissue: Group 1 < 30%; Group 2, 30% to 50%; and Group 3, > 50%. Each patient was re-evaluated 3 months after surgery. We assessed the international prostatic symptom score, nocturia and serum prostate specific antigen levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 20 publications
4
23
1
1
Order By: Relevance
“…Although surgical or interventional therapy is not indicated for nocturia, transurethral resection of the prostate (TURP) appears to confer a greater improvement in BPH symptoms including nocturia, and several studies reported a decrease in the mean number of nocturia episodes after TURP [35,36]. The mechanism of improvement in symptoms after TURP is not clear.…”
Section: Managementmentioning
confidence: 99%
“…Although surgical or interventional therapy is not indicated for nocturia, transurethral resection of the prostate (TURP) appears to confer a greater improvement in BPH symptoms including nocturia, and several studies reported a decrease in the mean number of nocturia episodes after TURP [35,36]. The mechanism of improvement in symptoms after TURP is not clear.…”
Section: Managementmentioning
confidence: 99%
“…21,22 The recommended TURP technique consists of a complete resection of adenomatous tissue inside the surgical capsule for better result in terms of quality of life and symptom improvement. 23 However prolonged TURP in medically compromised patients with large prostate may be associated with increased bleeding and TUR syndrome development. 23 We found the significant difference in preoperative QoL in patients having smaller prostate in comparison to that of patient group having large (> 80 grams) prostate size.…”
mentioning
confidence: 99%
“…23 However prolonged TURP in medically compromised patients with large prostate may be associated with increased bleeding and TUR syndrome development. 23 We found the significant difference in preoperative QoL in patients having smaller prostate in comparison to that of patient group having large (> 80 grams) prostate size. However after complete resection of adenomatous tissue in both groups, the QoL score after TURP shows no difference between both groups.…”
mentioning
confidence: 99%
“…10 Prostatectomy (transurethral or open surgical way) is the gold standard treatment of BPO when medical treatments are ineffective or responsible for side effects, depending on the patientʼs general status and the severity of the symptoms. A large number of studies [11][12][13][14] have shown an improvement of nocturia after outlet reduction surgeries in pure F I G U R E 1 Causative factors of nocturia S112 | groups of patients with BPO-induced nocturia. However, in some cases, symptoms persist or de novo symptoms appear.…”
Section: Nocturiamentioning
confidence: 99%